PENINGKATAN HASIL BELAJAR PESERTA DIDIK DENGAN MENGGUNAKAN MEDIA TEKA-TEKI SILANG PADA MATA PELAJARAN IPS DI KELAS III SDN 50 BULU’ DATU KOTA PALOPO - Sarti Sarti (Fakultas Tarbiyah dan Ilmu Keguruan, 2019)
The main problem in this study is the lack of learning motivation of students in the implementation of learning in social studies subjects in class III SDN 50 Bulu 'Datu, which amounts to 23 students. Sources of data in this study were obtained directly from students and teachers of class III SDN Bulu’ Datu. Data collection techniques are carried out using observation, tests, interviews, and documentation. Data processing and analysis techniques used are analysis quantitative data and qualitative data. The results showed that: with the application of the crossword puzzle media the students' learning outcomes each cycle had increased. Based on student learning outcomes test of class III SDN Bulu’ Datu conducted in two cycles shows that the learning outcomes of students have increased, from cycle 1 the average value is 88 with a percentage of 100% completeness, while cycle II has an average score of 93 with a percentage of 100% and has met the KKM which is 70. Thus the results of this study can be concluded that, using the medium of crossword puzzles on social studies subjects can improve student learning outcomes.